Governance and National Culture as Contingency Factors in Corporate Performance and Sustainability Outcomes: Evidence from the BRICS Economies - Luza, Bruna; Falconi, Tamara Goncalves; Zanchet, Aladio; Vesco, Delci Grapegia Dal (Indonesian Journal of Sustainability Accounting and Management, 2026)
This study investigates the influence of national governance on firm performance in BRICS economies, with culture as a moderating variable. The analysis is based on a balanced panel of 1,238 publicly traded firms from nine countries over the 2014–2023 period and employs three-level hierarchical linear models estimated in Stata® to account for firm-, year-, and country-level heterogeneity. The results indicate that national governance does not produce a homogeneous or systematically positive effect on corporate performance, as the estimated coefficients differ in magnitude and direction across governance dimensions and performance indicators. Furthermore, the findings reveal that national culture significantly moderates the governance–performance nexus, either reinforcing or weakening governance effects according to each country’s cultural configuration. These results are consistent with contingency theory, suggesting that governance effectiveness is not universal but shaped by the alignment between institutional quality and cultural context. From a sustainability perspective, the evidence indicates that governance quality and cultural attributes shape the institutional environment in which firms develop strategies, create value, and sustain long-term performance. In practice, the study suggests that governance models should be context-sensitive and adapted to each country’s institutional and cultural specificities rather than being uniformly transferred across settings.